University training and education initiatives to understand “Costa Rica Green". An educational proposal from a historical discipline. - Pizarro Méndez, Yanina (2016)
This article describes the teaching experience developed in the Environment History of Costa Rica course; an optional course given at the School of History for the environmental training of university students, between 2013 and 2015, as a maturity corollary of the Monitoring committee of Environmental Agro-ecological History. For this, it is needed a renewed point of view of the environmental education, taking into account old educative conceptions and new postulates of the Costa Rica teaching practice. To explain these processes, different sources were used, and the techniques implemented during the course are described in a general way. In this regard, under the historical investigative research experience, this article underlines the transcendence of new teaching ways.